MANAGEMENT OF MARKETING ACTIVITIES OF THE HOTEL AND RESTAURANT BUSINESS ENTERPRISE - MOSKVYAK, YAROSLAVA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the article the analysis concerning necessity of use of marketing in activity of a hotel - restaurant complex is carried out, the maintenance of marketing in system of management of the hotel enterprise is investigated.The main trends in the development of the hotel industry in Ukraine are substantiated. The main factors influencing the process of forming the hotel business in the country and determining the main directions for the development and improvement of the efficiency of the hotel and restaurant industry with the use of communications are studied. It is determined that the approach to marketing communications as an object of management implies the need to pay considerable attention to the organization of communication activities, intensification of advertising and information work both at the enterprise and with other actors in the tourism market. It is determined that to create such a management shell, allows to increase communication at the national integrated and corporate level. In the marketing system, enterprise awareness is important because any marketing activity is based on knowledge of the specific situation in the market. The organization of marketing activities should be based on the information system. The scheme of planning of marketing activity of the enterprise is resulted. The basic approaches according to which the enterprises carry out the marketing activity are defined.
Keywords: marketing; management; hotel industry; hotel business; tourism; investment attractiveness; development strategy; marketing communications